2018
DOI: 10.1002/csr.1645
|View full text |Cite
|
Sign up to set email alerts
|

The influence of corporate social responsibility on air pollution: Analysis of environmental regulation and eco‐innovation effects

Abstract: Air pollution is one of the most serious environmental problems affecting the general population's health and wellbeing. This article analyses the role companies and public‐sector institutions play in reducing air pollution. Corporations are motivated by a social commitment and the need to improve their productive processes, while public bodies endeavour to reduce air pollution to improve citizens' quality of life. This paper drills down into the impact of eco‐innovation as a mechanism for companies to achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 117 publications
0
43
0
4
Order By: Relevance
“…Measurements considered criteria of perception, opinion, and qualification through Likert‐type scales. Some studies reported environmental regulation evaluations using international scales to compare the effectiveness between countries that partake in organizations such as the OECD (Hwang & Kim, 2017; Jiménez, Martínez, & Godos, 2018; Naughton, 2014) or the European Union (Cló, Ferrais, & Florio, 2017; Galeotti, Rubashkina, Salini, & Verdolini, 2018; Galinato & Chouinard, 2018). Evaluations are useful for responding to global problems such as global warming; they can work as a source of information when adjusting international treaties and agreements with environmental impact.…”
Section: Methods For the Literature Review And Resultsmentioning
confidence: 99%
“…Measurements considered criteria of perception, opinion, and qualification through Likert‐type scales. Some studies reported environmental regulation evaluations using international scales to compare the effectiveness between countries that partake in organizations such as the OECD (Hwang & Kim, 2017; Jiménez, Martínez, & Godos, 2018; Naughton, 2014) or the European Union (Cló, Ferrais, & Florio, 2017; Galeotti, Rubashkina, Salini, & Verdolini, 2018; Galinato & Chouinard, 2018). Evaluations are useful for responding to global problems such as global warming; they can work as a source of information when adjusting international treaties and agreements with environmental impact.…”
Section: Methods For the Literature Review And Resultsmentioning
confidence: 99%
“…Previous studies have shown that CSR has a positive impact on reducing pollution, and this influence is reinforced when environmental regulation is developed [50]. Therefore, many governments have attempted to create more sensitive environments with regard to social and environmental problems, and they have sent signals to corporations that they should strengthen their commitment to environmental issues [51].…”
Section: Discussion Of Statistical Resultsmentioning
confidence: 99%
“…According to Demirel and Kesidou (2011), voluntarily implemented behaviors have positive influences on firms' environmental practices though. Because CSR is voluntary (Antonioli & Mazzanti, 2009), it might drive the adoption of innovations that pursue environmental goals (Jiménez-Parra, Alonso-Martínez, & Godos-Díez, 2018;Surroca, Tribo, & Waddock, 2010). In turn, sustainable innovations include environmental practices, so we predict that CSR may drive the adoption of sustainable innovation too.…”
Section: Link Between Csr and Innovationmentioning
confidence: 96%